"Ophelia; Do not believe his vows; they are brokers!" A Study of Unrewarded Love in Selected Shakespeare's Tragic Plays (Journal of the College of Basic Education, 2024)
Along with the great deal of academic works of analyses concerning the tragic plays of William Shakespeare (1564-1616), the study tries to make a different view of critical perusal regarding the selected great tragic plays of Shakespeare. It portrays the condition of unrewarded (one-sided or unrequited) love profitless passions that never being appreciated or even considered by some of the main characters in the selected pure tragic plays of Shakespeare as A.C. Bradley (1851-1935) considered, including Hamlet, Othello, Romeo and Juliet, Macbeth, and King Lear due to their picturing of the continuous struggle for different goals and reasons in their plots which concern both individuals and communities as well. The findings contribute to a broader appreciation of Shakespeare's artistic genius in capturing the intricacies of human emotions and relationships, presenting an enduring depiction of love's complexities and its potential for heartbreak. As a result, this study offers valuable insights into the enduring relevance of Shakespeare's tragedies, enriching our understanding of human nature and the enduring themes of unrewarded (unreciprocated) love that continue to captivate audiences to this day. The study relies on analytical approach to draw deeper analyses of characters and adopts MLA style for documentation, and ends up with the conclusions and works cited.